2014
DOI: 10.1055/s-0034-1390350
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Perinatal Factors in Short- and Long-Term Outcomes of Infants Born at 23 Weeks of Gestation

Abstract: Multiple perinatal factors significantly influence outcomes at the threshold of viability.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 21 publications
0
4
0
Order By: Relevance
“…Across follow-up ages, the prevalence of any NDI in North America was 8%–59%. The prevalence of moderate NDI was 39% in the single North American study that reported moderate NDI, 27 versus 3%–19% in included European studies. A meta-analysis that included birth cohorts in a median year of 2000 or later (median age at assessment, 28 months) estimated that 52% of surviving infants born extremely preterm worldwide develop NDI (defined as cognitive, motor, hearing, and visual impairment) to some degree; 86 this is in line with the NDI prevalence in North America found in the present SLR of more recent data.…”
Section: Discussionmentioning
confidence: 85%
See 3 more Smart Citations
“…Across follow-up ages, the prevalence of any NDI in North America was 8%–59%. The prevalence of moderate NDI was 39% in the single North American study that reported moderate NDI, 27 versus 3%–19% in included European studies. A meta-analysis that included birth cohorts in a median year of 2000 or later (median age at assessment, 28 months) estimated that 52% of surviving infants born extremely preterm worldwide develop NDI (defined as cognitive, motor, hearing, and visual impairment) to some degree; 86 this is in line with the NDI prevalence in North America found in the present SLR of more recent data.…”
Section: Discussionmentioning
confidence: 85%
“…The prevalence of severe NDI ranged from 12% to 27% across all follow-up durations (reported in four studies). 23,27,28,37 The prevalence of any CP was 8%–54% at 18 months to 2 years follow-up, 19,23,31,32 5%–11% between 2 and 5 years follow-up, 35,37 and 7% at ≥5 years follow-up. 40…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations